The Essence Of Teachers In Education Visions Through Optimization Management Of Character Education In Students - Marini, Mai (Tartib: Jurnal of Educational Management, 2022)
Education in Indonesia through the 2013 curriculum has character core values. All levels of education in the planning and process must be oriented towards creating Indonesian people with character. The teacher's role as the main agent of education is very important. Character education must start from a character teacher. This paper discusses the profile of teachers who are able to optimize character education management in students. In particular the main model of character teachers is the Prophet Muhamamd S.A.W. The approach used in this research is qualitative with the library research method. Data analyzed from literature. This research found that the four main characters of the Prophet Muhammad S.A.W. is an absolute requirement that must be met by a teacher. The success of the Prophet Muhammad in carrying out character education because he was an example. To optimize the management of character education in students, a teacher must be smart/fathonah, honest /shidiq, responsible/trustworthy and communicative/tabligh.